Baculites thomi Reeside, 1927, an Upper Cretaceous ammonite in the Western Interior of the United States - Cobban, W; Kennedy, W (1991)
The heteromorphic ammonite Baculites is an important marker fossil for much of the marine Upper Cretaceous of the Western Interior of the US. Baculites thomi Reeside, 1927, is a previously poorly known species that is herein redescribed from well-preserved material from the top of the Kevin Member of the Marias River Shale in northwestern Montana. The species ranges from the upper Santonian into the lower Campanian. -Authors